2021
DOI: 10.1016/j.bios.2021.113286
|View full text |Cite
|
Sign up to set email alerts
|

An intelligent face mask integrated with high density conductive nanowire array for directly exhaled coronavirus aerosols screening

Abstract: The current ongoing outbreak of Coronavirus Disease 2019 (COVID-19) has globally affected the lives of more than one hundred million people. RT-PCR based molecular test is recommended as the gold standard method for diagnosing current infections. However, transportation and processing of the clinical sample for detecting virus require an expert operator and long processing time. Testing device enables on-site virus detection could reduce the sample-to-answer time, which plays a central role in containing the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 38 publications
0
45
0
Order By: Relevance
“…With the use of nanowires, there are advantages such as ultra-low power consumption; small size; rapid response; high sensitivity; and being non-hazardous, easy to use, non-invasive, stored well and not that costly. For the management and detection of respiratory infections, a sensitive and affordable POC tool was provided as a combination of nanoscale sensors and a face mask [ 157 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the use of nanowires, there are advantages such as ultra-low power consumption; small size; rapid response; high sensitivity; and being non-hazardous, easy to use, non-invasive, stored well and not that costly. For the management and detection of respiratory infections, a sensitive and affordable POC tool was provided as a combination of nanoscale sensors and a face mask [ 157 ].…”
Section: Discussionmentioning
confidence: 99%
“…In approximately 5 min, viral concentrations as low as 7 pfu/mL were detected from an atomized sample of coronavirus aerosol mimic. The POC systems can be used on-site for basic screening of coronavirus infections and may aid in understanding the course of COVID-19 while a patient is on treatment [90]. A cotton-tipped electrochemical immunosensor for detecting the virus antigen of the SARS-CoV-2 was developed by Eissa et al [90].…”
Section: Wearable Microfluidic and Smart (Nano)biosensorsmentioning
confidence: 99%
“…Based on micro/nano technologies and the principle of immunoassay, some POCT platforms are constructed directly for detection of infectious pathogens waiving nucleic acid amplifications. Integrating the detection devices into wearables can expand opportunities for long-term and noninvasive monitoring of infections [ 158 , 159 ]. Xue et al reported an intelligent wearable face mask integrated with a flexible immunosensor for highly sensitive screening of exhaled coronavirus aerosols.…”
Section: Micro/nano Devices For Point-of-care Testing Of Sars-cov-2mentioning
confidence: 99%